PENDAMPINGAN PEMBELAJARAN SOFT SKILL SANTRI DI PONDOK PESANTREN HIDAYATUSSIBYAN, BOWAN, TEMPURAN, MAGELANG - Laili Syarifah; Pungki Zifaradella (Sekolah Tinggi Agama Islam Syubbanul Wathon Magelang, 2021)
Education has an important role in human life and civilization. That education can be a bridge for the present and the future. Thus, conducting learning assistance is needed because the world is now moving fast at an increasingly fast pace. Knowledge is not the only way to determine whether someone is successful. However, it is necessary to have soft skills within yourself. Soft skill learning for students is trained with various skills and abilities of students to have a good mentality in the form of noble character and human attitude towards others. As a young professional and being someone who can be worked within a team, having soft skills is very important. Students must have the following soft skill elements, namely communication skills, thinking skills, problem-solving, and teamwork activities. Soft skills can also provide self-awareness in critical thinking, build self-confidence, empathy, and adapt to any condition. The form of training held at the Hidayatussibyan Islamic boarding school is to use direct practice methods